Millet Adoption in Bundelkhand, U.P.: Traditional vs. Emerging Crop Trends - OJHA, PANKAJ KUMAR; Saxena, Pragati; Fatma, Samreen; Babli Rani,; Kaur, Paramjeet; Ojha, Pragya; Yadav, Abhishek Kumar (Indian Journal of Extension Education, 2025)
The study, conducted between January and March 2023, investigated millet adoption patterns among 400 farmers in Bundelkhand, Uttar Pradesh, India, comparing traditional crop cultivation with emerging millet trends in Jalaun and Jhansi districts. The current study’s findings indicated that millets, driven by climate resilience (50%), market demand (37.5%), and nutritional value (12.5%), are cultivated by 37.5% of farmers, while traditional crops (wheat, rice, maize) dominate (62.5%) due to market reliability. Millets are consumed daily by 10%, primarily at breakfast (30%) and lunch (25%), enhancing nutritional security. Significant challenges to millet adoption include limited market access and awareness. ANOVA and Chi-square tests revealed significant differences in crop selection and consumption across gender (p